Environmental effects on the reliability of an AISI 304 structure - Racim Boutelidja; Abdelmoumene Guedri; Mohammed Amine Belyamna; Bachir Merzoug (Fracture and Structural Integrity)
This work is based on the application of probabilistic fracture mechanics (MRP) models to predict the reliability of pressure pipelines in nuclear power reactors. The simulation of cracking of stainless steel piping under the conditions of intergranular stress corrosion cracking (IGSCC) is based on the improved modified piping reliability analysis including seismic events (PRAISE) code. The IGSCC is characterized by a unique damage parameter that depends on residual stresses and environmental conditions. Case studies of IGSCC failures in nuclear power plants are presented and the contribution of environmental effects on crack initiation and leakage is discussed. For small damages we observed that the change in temperature or oxygen concentration does not affect the initiation process but their decrease contribute favourably to the decrease in the leakage probabilities.